Original paperProstate cancer boost using high-dose-rate brachytherapy: early toxicity analysis of 3 different fractionation schemes - Hijazi, Hussam; Chevallier, Daniel; Gal, Jocelyn; Chand, Marie-Eve; Gautier, Mathieu; Hannoun-Levi, Jean-Michel (Journal of Contemporary Brachytherapy, 2013)
Purpose : To analyse early toxicity of high-dose-rate brachytherapy (HDRB) boost for prostate cancer using 3 fractionation schemes. Material and methods: From February 2009 to May 2012, after the first course of external beam radiation therapy (EBRT 46 Gy/23 f), 124 patients underwent HDRB boost for low (7%), intermediate (19%), and high-risk (73%) prostate cancers. From February to December 2009, Group 1 (G1) = 18 Gy/3 f/2 d (24%); from January 2010 to April 2011, Group 2 (G2) = 18 Gy/2 f/2 d (42%), and from May to September 2011, Group 3 (G3) = 14 Gy/1 f/1 d (34%). Planning and CT-scan was performed before each fraction. Dose constraints for G1/G2 were V100 rectum = 0 and V125 urethra = 0, while for G3 V90 rectum = 0 and V115 urethra = 0. Genito-urinary (GU) and Gastro-intestinal (GI) acute toxicities were assessed at 1 month (for the 3 fractionation schemes) and 6 months (for 18 Gy/3 f and 18 Gy/2 f) after the boost (CTCv3.0). Results : Median follow-up was 25 months (8-46.9), median age was 71 years (50-82), and median CTV was 31 cc (16-71). The grades of acute GI and GU toxicities at 1 and 6 months after HDRB were mainly Grade 1 with few Grade 2 (GU: 5% at 1 month; GI: 1% at 6 months). One patient developed G4 sepsis toxicity 2 days after HDRB and recovered without after-effects. No significant differences were observed at 1 and 6 months after the HDRB between treatment groups. Conclusions : The right fractionation remains under discussion, but prostate cancer HDRB boost using a single fraction (providing similar results in terms of acute toxicity) is more comfortable for the patient, and less time consuming for the medical staff.